2011
DOI: 10.1038/onc.2011.566
|View full text |Cite
|
Sign up to set email alerts
|

Mcm2 deficiency results in short deletions allowing high resolution identification of genes contributing to lymphoblastic lymphoma

Abstract: Mini-chromosome maintenance (Mcm) proteins are part of the replication licensing complex that is loaded onto chromatin during the G1-phase of the cell cycle and required for initiation of DNA replication in the subsequent S-phase. Mcm proteins are typically loaded in excess of the number of locations that are utilized during S-phase. Nonetheless, partial depletion of Mcm proteins leads to cancers and stem cell deficiencies. Mcm2 deficient mice, on a 129Sv genetic background, display a high rate of thymic lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 39 publications
4
52
0
2
Order By: Relevance
“…In two of our tumors with MCM4 mutations, this association could be defined mechanistically by genomic alteration of the family of MCM2-7 genes (43). Consistent with this hypothesis, prior studies have shown that Mcm protein deficiencies result in high rates of cancer in mouse models (44,45), catastrophic chromosomal rearrangements in human lymphoblasts in culture (46), and complex chromosomal alterations at discrete locations that are consistent with chromothripsis (43).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In two of our tumors with MCM4 mutations, this association could be defined mechanistically by genomic alteration of the family of MCM2-7 genes (43). Consistent with this hypothesis, prior studies have shown that Mcm protein deficiencies result in high rates of cancer in mouse models (44,45), catastrophic chromosomal rearrangements in human lymphoblasts in culture (46), and complex chromosomal alterations at discrete locations that are consistent with chromothripsis (43).…”
Section: Discussionsupporting
confidence: 60%
“…Previously, we have suggested that the frequent, short intrachromosomal DELs spanning 500 kbp or less that occur in mouse tumors resulting from deficient Mcm2 protein levels could result from failure to rescue stalled replication forks within individual replication factories (43). This mechanism may also help to explain the frequent localization of multiple translocation events seen in individual tumors in the present study.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The genetic lesions occurring in these tumors have been characterized and are predominately focal deletions averaging ∼450 kbp in length (Rusiniak et al 2012). To examine the possibility that origin usage in MEFs is reduced near locations where deletions are found in tumors of MCM2-deficient mice, we compared the NSCR wt minus MCM2-deficient wiggle file in the UCSC Genome Browser to locations of the previously identified deletions from tumors arising in MCM2-deficient mice (e.g., Supplemental Fig.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…The licensing of dormant origins is postulated to serve as a backup system to allow completion of replication in the event of replication fork stalling (Woodward et al 2006;Ge et al 2007;Ibarra et al 2008). The importance of sufficient DNA replication origin licensing to the maintenance of genome stability is demonstrated by the high rates of cancer incidence in mice in which MCM levels or function are reduced (Pruitt et al 2007;Shima et al 2007;Kunnev et al 2010;Kawabata et al 2011;Rusiniak et al 2012). Further, under conditions in which the demand for cell proliferation is high, or where cells are transitioning from a low to an accelerated rate of growth, MCM levels have been shown to be limiting, resulting in a reduced level of primary or dormant origin licensing (Orr et al 2010).…”
mentioning
confidence: 99%